Keputusan Investasi Digital dan Transaksi non Tunai Investor Muslim di Kabupaten Sukoharjo - Arif, Yulfan; Rina Sari Qurniawati (Journal Of Islamic Economics And Finance, 2022)
Muslim investors invest for financial gain in the future. The current investment decision determines the profit or loss received. The purpose of the study was to determine how much financial literacy and risk tolerance influence in determining digital investment decisions and to find out how much financial literacy and risk tolerance influence in conducting non-cash transactions during the covid-19 pandemic for Muslim investors. The research was conducted on Muslim investors in Sukoharjo Regency. Determination of the sample using purposive sampling with the number of respondents as many as 110. Data collection was done using a questionnaire distributed to Muslim investors who have done investment activities. Testing the model using Path Analysis with SmartPLS Software by performing Individual Item Reliability Test, Internal Consistency Test, and Discriminant Validity Test. The test results show that the financial literacy of Muslim investors has no effect on investment decisions and non-cash transaction decisions. Meanwhile, risk tolerance affects investment decisions and non-cash transaction decisions. The investment decisions of a Muslim are not based on their financial knowledge but on the current economic situation